(untitled) (REMUNOM, 2024)
Premature Placental Abruption is a serious medical condition that occurs during pregnancy when the placenta partially or completely detaches from the uterus before the baby’s birth. This condition can pose a threat to both the mother and the fetus. It is a literature review, a method that provides the synthesis of knowledge and the incorporation of the applicability of results from significant studies into practice. The present study aims to address the provision of nursing services in the face of signs of premature placental abruption. The role of nursing in the face of premature placental detachment is crucial to ensuring the safety and well-being of both the mother and the fetus. Nursing must be attentive to the signs and symptoms of premature placental abruption and ready to act swiftly in case of an emergency. The multidisciplinary approach, involving not only the nurse but the entire healthcare team, is essential to ensure the well-being of the pregnant woman and the fetus. Identifying signs and symptoms, conducting examinations, and promptly making decisions are fundamental aspects of appropriate care for women experiencing premature placental abruption.